Individual Differences in Vertebrate Behavioural Lateralisation: The Role of Genes and Environment - Bisazza, Angelo; Lucon-Xiccato, Tyrone (Symmetry (Basel), 2025)
In humans, certain functions such as language and spatial attention are lateralised, meaning they are predominantly or exclusively performed by one hemisphere. Intriguingly, a significant portion of individuals exhibit a mirrored pattern of asymmetry, which has been attributed to genes, environmental influences, or other factors. As lateralisation occurs across all major groups of vertebrates, literature in other species might provide valuable insights into these mechanisms. We reviewed current knowledge on the genetic and environmental factors underlying individual variability in lateralisation in non-human vertebrates. Evidence of a genetic basis for the direction, strength of asymmetries, or both has been reported in about a dozen species of fish and mammals. Nevertheless, a careful examination revealed that none of these studies can definitively exclude the influence of non-genetic factors. On the other hand, studies from the past decade have suggested that environmental factors can shape both the direction and strength of lateralisation in adaptive ways, aligning the individual’s phenotype with local environmental conditions. Overall, this review supports the potential role of both genetic differences and environmentally driven plasticity in shaping lateralisation variance while highlighting literature gaps that prevent a precise disentanglement of the roles of these factors.